2020
DOI: 10.1111/odi.13751
|View full text |Cite
|
Sign up to set email alerts
|

Andrographolide‐loaded solid lipid nanoparticles enhance anti‐cancer activity against head and neck cancer and precancerous cells

Abstract: Background: Increasing evidence indicates that andrographolide (ADG) exhibits anticancer activity against various cancer cell lines. However, its high hydrophobicity and poor bioavailability restrict its clinical application as a chemopreventative agent.Previously, we have shown that ADG-loaded solid lipid nanoparticles (SLNs) significantly enhanced the bioavailability and anti-hyperlipidemic activity of ADG. Objectives:We aimed to investigate whether ADG-SLN enhanced the bioavailability and anti-cancer effica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…(23). Nanoparticle-mediated delivery is a promising approach to enhance bioavailability and increase the efficacy of several chemopreventive agents for OSCC (24)(25)(26)(27)(28). Our previous study clearly demonstrated that nano-SAB can enhance cellular uptake and anticancer efficacy in head and neck cancer cells, as well as in precancerous cells in vitro (8).…”
Section: Discussionmentioning
confidence: 99%
“…(23). Nanoparticle-mediated delivery is a promising approach to enhance bioavailability and increase the efficacy of several chemopreventive agents for OSCC (24)(25)(26)(27)(28). Our previous study clearly demonstrated that nano-SAB can enhance cellular uptake and anticancer efficacy in head and neck cancer cells, as well as in precancerous cells in vitro (8).…”
Section: Discussionmentioning
confidence: 99%
“…This study showed that in the presence of encapsulated ADG (ADG-SLN), compared to free ADG, the 50% inhibitive concentrations (IC 50 ) against HIOEC, Leuk1, and HN6 and HN30 cells are much lower. Moreover, the results also showed higher efficacy cell cycle arrest and apoptosis, which reveals that the use of SLNs as nanocarriers promotes therapeutic success [ 109 ].…”
Section: Nanocarriers For Hnc Diagnosis and Treatmentmentioning
confidence: 99%
“…Sanati et al [42] reported successful inhibition of neuroblastoma and cervical cancer cells by nano-encapsulation of the rich extracts of AGL. Further, AGLloaded solid lipid nanoparticles inhibited head and neck cancer [43]. Andrographolide-loaded nanocochleates were assessed for their physiochemical properties to be used as an oral delivery alternative for clinical trials in cancer therapy [44].…”
Section: Functional Prospective Of Andrographolide (Agl) On Human Healthmentioning
confidence: 99%